ANALISIS USAHATANI TANAMAN ANGGREK DENDROBIUM DENI ERIANTO DI KECAMATAN KULIM KOTA PEKANBARU PROVINSI RIAU - Malik Kautsar Wijaya; Ilma Satriana Dewi (UIR Press, 2024)
Orchids are valued ornamental plants that offer significant aesthetic appeal. They can be cultivated as a viable source of income for farmers. However, successful care and maintenance of orchids require specialized skills. Improper cultivation techniques can lead to plant death, negatively impacting farmers' earnings. This research aims to analyze two key aspects: 1. The application of production factors and cultivation technology, and 2. The farming dynamics, including production costs, output, income, and efficiency at the Deni Erianto Qanita Orchid Nursery for Dendrobium orchid plants. The study was conducted at the Qanita Orchid Nursery in Kulim District, Pekanbaru City, Riau Province, using a survey method over a six-month period from July to December 2023. The respondents included one entrepreneur and three employees, selected through a census sampling technique. The research utilized both primary and secondary data, which were then analyzed both descriptively, qualitatively, and quantitatively. Findings indicate that the production factors for orchid cultivation encompass 1 hectare of land, 1,000 seedlings, 4,200 ml of QC Gen 2 fertilizer, 800 ml of QC HD, and 1,400 ml of QC Gen 3. Additionally, 1,000 ml of Samite pesticide is utilized each month, along with 40 liters of Pertalite gasoline. The technology employed in orchid cultivation involves several stages, including land preparation, plant propagation, selection of growing media, planting, maintenance, pest management, and harvesting. The analysis of farming costs revealed a total expenditure of Rp. 25,799.72 per hectare per month. The overall production is 150 sticks per month, priced at IDR 250,000 per stick, resulting in a gross income of Rp. 37,500,000 per hectare per month, and a net income of Rp. 11,700,928 per hectare per month. The Return Cost Ratio (RCR) for orchid farming is determined to be 1.45.